Honoring diverse teaching styles : a guide for supervisors - Pajak, Edward, 1947- (Association for Supervision and Curriculum Development, 2003)
In this era of increasing teacher accountability, helping novice and veteran teachers succeed in the classroom has never been more urgent or more challenging. Honoring Diverse Teaching Styles is essential reading for anyone who wants to help teachers meet today's performance standards while also respecting the unique gifts each teacher brings to the classroom. This concise guide provides the background and creates a system for fostering effective teacher development, and includes: Descriptions and examples of the four basic styles of teaching; Tips for matching your communication style with the teacher's preferred style; Tools for effectively observing classroom practice; Ideas for helping teachers build on their strengths while exploring different ways of teaching. Teachers will broaden their instructional repertoire and develop a stronger professional identity as they discuss effective practice with an experienced teacher. They will become more confident in their decision making and take greater command of the classroom. Educators who are new to providing clinical support will find this a highly readable guide to the wide range of strategies available; experienced educators will discover new ways to strengthen their own practice and rethink their observational methods; and all will gain the satisfaction of helping teachers develop the kind of expertise that truly fosters student achievement. Edward Pajak is a professor and chair of the Department of Teacher Development and Leadership at Johns Hopkins University.